Durability life prediction and horizontal bearing characteristics of CFRP composite piles in marine environments. (27th February 2023) - Shao, Wei; Sun, Quanxing; Xu, Xu; Yue, Wenhan; Shi, Danda
Highlights: The corrosion initiation time and reinforcement corrosion depth of CFRP composite piles are predicted. The degradation model of bending stiffness of CFRP composite piles is established. The flexural stiffness reduction factor of CFRP composite piles is obtained by conducting the model pile bending tests. The horizontal bearing characteristics of CFRP composite piles in marine environments is analyzed. Abstract: In this paper, the durability life and horizontal bearing characteristics of carbon fiber reinforced polymers (CFRP) composite piles in marine environments are studied. The durability life of CFRP composite piles is divided into the initial corrosion stage of reinforcement and the crack propagation stage of concrete protection layer. The chloride diffusion model and Monte Carlo simulation method are used to predict the initial corrosion time of CFRP composite piles. Based on the thick-walled cylinder theory, the critical corrosion depth of the reinforced steel corresponding to the cracking of concrete protective layer is deduced. The durability life prediction model of crack propagation stage is established. The flexural stiffness reduction factor of CFRP composite piles with different replacement ratios is obtained by conducting the model pile bending tests. The attenuation law of bending stiffness and horizontal bearing characteristics of CFRP composite piles in marine environments are analyzed. The results show that the higher the replacement ratio of CFRP bar, the slower the reduction rate of flexural stiffness of CFRP composite pile is. Under the same buried depth, the pile bending moment and shear force of CFRP composite piles decrease with the increase of CFRP reinforcement replacement ratio. The horizontal displacement of CFRP composite piles increases with the increase of CFRP reinforcement replacement ratio.